PENINGKATAN KEMAMPUAN BERKOMUNIKASI DALAM BAHASA INGGRIS SETARA LEVEL ELEMENTARY DENGAN STUDENT TEAM – ACHIEVEMENT DIVISION SISWA KELAS IX E MTs. NEGERI REJOSARI KABUPATEN MADIUN TAHUN PELAJARAN 2011/2012 - Moch. Fathoni (IKIP PGRI MADIUN, 2015)
A person's ability to communicate can be demonstrated in two ways, namely oral communication and written one. If the communication takes place verbally, there are other elements that need to be considered by the teacher, and of course the need to be taught to the students, which is about the speech or pronunciation. Moreover, Spelling and Pronounciation differ greatly, for example, a person who uttered procedure with speech would not be understood by those who pronounce the word correctly. Similarly, if the person is listening to the speech of others who pronounce it correctly, certainly not the word that he had captured the word. Formulation of the problem in this research is: Is there an ability increasing to communicate in English through Student Team Achievement Division equivalent to the elementary school students of MTs. Rejosari Madiun in the Schooling Year 2011/2012? In this study, Researcher collaborates with other teachers and the principals. Researcher is involved in the study from the beginning to the end of the study. Researcher is trying to see, observe, feel, live, reflect and evaluate learning activities. The stages of research consist of planning, acting, observing and reflecting. The study collected data were statistically analyzed using the formula that is mean or average to get accurate results. From the analysis and observations on this study the result showed that the average value of the cycle has increased significantly. Referring to the formulation of the problem and the hypothesis of action proposed in this Classroom Action Research it can be concluded that: There is an ability increasin the communication competence to the elementary school students of MTs Rejosari Madiun through Student Team Achievement Division in the Schooling Year 2011/2012.